2011
DOI: 10.1074/jbc.m111.266619
|View full text |Cite
|
Sign up to set email alerts
|

SlyA Protein Activates fimB Gene Expression and Type 1 Fimbriation in Escherichia coli K-12

Abstract: We have demonstrated that SlyA activates fimB expression and hence type 1 fimbriation, a virulence factor in Escherichia coli. SlyA is shown to bind to two operator sites (OSA1 and OSA2), situated between 194 and 167 base pairs upstream of the fimB transcriptional start site. fimB expression is derepressed in an hns mutant and diminished by a slyA mutation in the presence of H-NS only. H-NS binds to multiple sites in the promoter region, including two sites (H-NS2 and H-NS3) that overlap OSA1 and OSA2, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…In addition, there is also a SNP present in slyA , which encodes a known transcriptional regulator of virulence genes. SlyA is involved in conferring resistance to antimicrobial peptides and oxidative stress in salmonellae [31], [32] as well as regulation of fimbriae in E. coli , which have an important role in colonization and pathogenesis [33]; based on the crystal structure of SlyA, the resulting amino acid change (V120G) is located between two α-helices involved in dimerization [34]. Although the functional consequences of these mutations are not directly known, it is interesting that they occurred during 18 months of intra-abdominal carriage after an initial outbreak event that resulted in patient deaths.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is also a SNP present in slyA , which encodes a known transcriptional regulator of virulence genes. SlyA is involved in conferring resistance to antimicrobial peptides and oxidative stress in salmonellae [31], [32] as well as regulation of fimbriae in E. coli , which have an important role in colonization and pathogenesis [33]; based on the crystal structure of SlyA, the resulting amino acid change (V120G) is located between two α-helices involved in dimerization [34]. Although the functional consequences of these mutations are not directly known, it is interesting that they occurred during 18 months of intra-abdominal carriage after an initial outbreak event that resulted in patient deaths.…”
Section: Resultsmentioning
confidence: 99%
“…H-NS regulates the transcription of several UPEC genes by competing for binding to their promoter element with a MarR-type regulatory protein; this includes SfaX binding to the sfa 2 fimbrial promoter (80), PapX binding to the flhDC flagellum master regulator promoter (92), and SlyA binding to the type 1 fimbria fimB recombinase promoter (93). The SfaX and PapX regulator genes are cotranscribed as part of their respective upstream fimbrial operon (encoding S-and P-type fimbriae, respectively [47,80]).…”
Section: Transcription Of the Vat Gene Is Directly Repressed By H-nsmentioning
confidence: 99%
“…Levels of fimB expression were highest in a neutral pH/low osmolality condition and lowest in a low pH/high osmolality medium. A switch from a neutral pH/low osmolality environment that favours fimB activation by SlyA (a proposed activator of fimB transcription, McVicker et al, 2011) or RcsB (another proposed activator of fimB transcription, Schwan et al, 2007) to a low pH/high osmolality environment found in the human urinary tract that favours OmpR could have relevance in regulating fimB (Schwan, 2011). OmpR could displace SlyA or RcsB on the fimB promoter site as the OmpR level increases in UPEC growing in an acidic/high osmolality environment.…”
Section: Discussionmentioning
confidence: 99%